2008
DOI: 10.1002/jmri.21602
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of dynamic contrast‐enhanced MRI in monitoring radiation‐induced changes in the fraction of radiobiologically hypoxic cells in human melanoma xenografts

Abstract: Purpose:To investigate the potential of gadopentetate dimeglumine (Gd-DTPA)-based dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) in detecting radiation-induced changes in the fraction of radiobiologically hypoxic cells in A-07 human melanoma xenografts. Materials and Methods:A-07 tumors were randomly assigned to an unirradiated control group or a group given a single radiation dose of 20 Gy. DCE-MRI and measurement of fraction of hypoxic cells were performed immediately before and 24 h after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The hypoxic tumor fraction may increase shortly after radiation exposure because aerobic cancer cells are inactivated, whereas the hypoxic cancer cells survive. To investigate whether K trans and/or v e are sensitive to radiation-induced hypoxia, we subjected melanoma xenografts to DCE-MRI before (day 0) and after (day 1) radiation exposure [40]. Although the hypoxic fraction increased after irradiation, no changes in K trans nor v e were observed ( Figure 5).…”
Section: K Trans Is Insensitive To Radiation-induced Hypoxiamentioning
confidence: 99%
“…The hypoxic tumor fraction may increase shortly after radiation exposure because aerobic cancer cells are inactivated, whereas the hypoxic cancer cells survive. To investigate whether K trans and/or v e are sensitive to radiation-induced hypoxia, we subjected melanoma xenografts to DCE-MRI before (day 0) and after (day 1) radiation exposure [40]. Although the hypoxic fraction increased after irradiation, no changes in K trans nor v e were observed ( Figure 5).…”
Section: K Trans Is Insensitive To Radiation-induced Hypoxiamentioning
confidence: 99%
“…It was also shown that hypoxia estimated by 18 F-FMISO-PET correlated negatively with Ktrans from DCE-MRI in animal models, in head and neck cancers and in breast tumors, supporting the use of DCE-MRI to measure perfusion-driven hypoxia (Cho et al, 2009;Simoncic et al, 2017;Carmona-Bozo et al, 2021). However, several important limitations were also noted (Benjaminsen et al, 2008;Gulliksrud et al, 2010;Jordan and Gallez, 2010;Borren et al, 2013), including the absence of correlation of DCE-MRI parameters with the expression of HIF-1α and HIF-2α (Øvrebø et al, 2012). It should be emphasized that DCE-MRI takes only into account the perfusion without consideration to the oxygen consumption that plays also an important role in the establishment of tumor hypoxia.…”
Section: Magnetic Resonance Imaging With Exogenous Contrastmentioning
confidence: 83%